Adsorption Kinetic Models Applied to Nickel Ions on Hazelnut Shell Activated Carbons - M. Kobya; E. Demirbał; M.S. Öncel; S. Łencan (Adsorption Science & Technology)
Kinetic models describing the adsorption of Ni(II) ions on to hazelnut shell active carbon (HSAC) have been compared. Kinetic studies have also been carried out in a batch adsorber over a range of initial metal ion concentration (11.87–92.34 mg/dm 3 ), agitation speed (50–200 rpm) and adsorbent particle size (0.90–1.60 mm). The rate models evaluated included the pseudo-first order equation, the pseudo-second order equation and the Elovich equation. The results obtained showed that the pseudo-second order kinetic model correlated the experimental data well and better than the other models examined in this study.